2010
DOI: 10.1007/s13238-010-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide bias of DCL and AGO in plant anti-virus gene silencing

Abstract: Plant Dicer-like (DCL) and Argonaute (AGO) are the key enzymes involved in anti-virus post-transcriptional gene silencing (AV-PTGS). Here we show that AV-PTGS exhibited nucleotide preference by calculating a relative AV-PTGS efficiency on processing viral RNA substrates. In comparison with genome sequences of dicot-infecting Turnip mosaic virus (TuMV) and monocot-infecting Cocksfoot streak virus (CSV), viral-derived small interfering RNAs (vsiRNAs) displayed positive correlations between AV-PTGS efficiency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 56 publications
(106 reference statements)
2
11
0
Order By: Relevance
“…The difference in DNA G+C content between coding regions and IRs (46.1 and 41.5%, respectively), could justify, at least partially, the limited accumulation of v-sRNAs in the AGV IR. Indeed, GC-rich regions were reported to be preferred for DCL activity (Ho et al, 2007), with data supporting that a decrease of viral DNA G+C content from 50 to 42% may negatively affect DCL targeting (Ho et al, 2010). A relatively similar higher accumulation of v-sRNAs in the coding regions and lower accumulation in the AU-rich IR was also reported previously in the case of CaLCuV, TYLCCNV and TYLCSV (Aregger et al, 2012;Miozzi et al, 2013;Yang et al, 2011).…”
Section: Characterization Of V-srnas Derived From Agvsupporting
confidence: 73%
“…The difference in DNA G+C content between coding regions and IRs (46.1 and 41.5%, respectively), could justify, at least partially, the limited accumulation of v-sRNAs in the AGV IR. Indeed, GC-rich regions were reported to be preferred for DCL activity (Ho et al, 2007), with data supporting that a decrease of viral DNA G+C content from 50 to 42% may negatively affect DCL targeting (Ho et al, 2010). A relatively similar higher accumulation of v-sRNAs in the coding regions and lower accumulation in the AU-rich IR was also reported previously in the case of CaLCuV, TYLCCNV and TYLCSV (Aregger et al, 2012;Miozzi et al, 2013;Yang et al, 2011).…”
Section: Characterization Of V-srnas Derived From Agvsupporting
confidence: 73%
“…Why certain AGO proteins might be more or less important for targeting different viruses is unclear. Recent reports have shown that the regions of a virus most effectively targeted by vsiRNAs do not necessarily correlate with those regions corresponding to the most abundant viRNAs (Szittya et al, 2010) and that AGO proteins show bias in the siRNAs they bind (Mi et al, 2008;Takeda et al, 2008;Ho et al, 2010). Thus, it is tempting to speculate that targeting by a given AGO protein may depend on a combination of the availability of the viral genome to RNA-silencing components, determined by RNA structure, together with the nucleotide composition of such regions.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that animal viruses may mutate to escape host antibody derived immunities (reviewed by [71]). Regarding host RNAi immunity (reviewed by [47,48]), viruses may also evolve to change their genome composition to reduce host RNAi response during infections [72-74]. Single nucleotide mutations were not considered as a feasible evolutionary strategy for viruses to combat the natural host RNAi because RNAi targets the whole of the virus genome simultaneously (e.g.…”
Section: Discussionmentioning
confidence: 99%